2003
DOI: 10.1046/j.1365-2222.2003.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immunoglobulin E responses in Balb/c mice against the major allergens of timothy grass (Phleum pratense) pollen

Abstract: The IgE reactivity induced by the major allergens in Balb/c mice was very similar to that found in allergic patients, with the exception of Phl p 1. The kinetics of the specific IgE response was comparable using either pollen extract or the purified major allergens, indicating that the intrinsic properties of the allergens are of importance rather than their proportionate amounts in pollen extract. This model should prove to be suitable for investigations regarding the mechanisms of induction and manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Sensitization was carried out by intraperitoneal injections of 5 µg recombinant Phleum pratense major allergen Phl p5 (Biomay, Wien, Austria) adsorbed to 1 mg Alum Imject (Pierce, Rockford, USA) on days 0, 14, and 21. Mice were finally challenged on days 28 and 29 intranasally with 9 µg Phleum pratense extract (Alk-Scherax, Wedel, Germany) in 50 µL PBS as described elsewhere [19].…”
Section: T-lymphocyte Proliferation Assaymentioning
confidence: 99%
“…Sensitization was carried out by intraperitoneal injections of 5 µg recombinant Phleum pratense major allergen Phl p5 (Biomay, Wien, Austria) adsorbed to 1 mg Alum Imject (Pierce, Rockford, USA) on days 0, 14, and 21. Mice were finally challenged on days 28 and 29 intranasally with 9 µg Phleum pratense extract (Alk-Scherax, Wedel, Germany) in 50 µL PBS as described elsewhere [19].…”
Section: T-lymphocyte Proliferation Assaymentioning
confidence: 99%
“…Strips incubated with the secondary antibodies alone served as negative controls. The major allergens which elicit an IgE response in BALB/c mice have been determined previously [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have described the IgE response of BALB/c mice to P. pratense pollen extract (PE) [9]and demonstrated that the IgE response to P. pratense allergens strongly resembles the one found in human patients, differing only in the lack of an IgE reactivity against Phl p 1 [9, 10]. To our knowledge, there is no study dealing with grass pollen allergens in association with the induction of IgE and ICHR to these clinically relevant allergens in different mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the dispersion of pine pollens is most intense for about 2 weeks, IgE induction experiments were conducted on mice for 15 days to induce allergic reactions via inhalation and skin application (Tamura 1986;Conford et al 1990;Maejima et al 2000;Mahler et al 2000;Seitzer et al 2003a, b;Mondoulet et al 2010Mondoulet et al , 2012Tordesillas et al 2015). Control mice showed no change in the IgE compositions of blood sera collected on days 5, 10, and 15 (Fig.…”
Section: Comparison Of Ige Induction By Pine Pollensmentioning
confidence: 99%